Nós conectam: slow design para a criação e experiência do fazer macramê - Muxfeldt, Ana Luisa (My University, 2025)
This work focuses on the value of handmade craftsmanship and the practice of the Slow Design movement, with a therapeutic emphasis on the macramé technique. It seeks to understand how the fast-paced rhythm of modern life and digitalization have contributed to issues such as anxiety and stress among young people. Highlighting the challenges of an accelerated world, the study explores how Slow Design can foster a more mindful and considerate process, offering significant therapeutic benefits. In this way, it became possible to more accurately identify the target audience, emphasizing the importance of the Slow movement combined with the joy of manual creation. This study proposes practical solutions that promote greater personal connection, stress reduction, and increased self-esteem through a conscious engagement with design and the manual art of macramé. [resumo fornecido pelo autor]
Este trabalho centra-se no valor do fazer manual e na prática do movimento Slow Design, com um foco terapêutico na técnica do macramê. Este trabalho busca entender como o ritmo acelerado da vida moderna e a virtualização contribuíram para questões como ansiedade e estresse entre os jovens. Destacando, a partir da problemática do mundo acelerado como o slow design pode promover um processo mais consciente e preocupado, oferecendo benefícios terapêuticos significativos. Desta forma, tornou-se possível identificar o público de forma mais assertiva, entendendo a importância do movimento slow aliado ao prazer do fazer manual. Este estudo propõe soluções práticas que promovam uma maior conexão pessoal, redução do estresse e aumento da autoestima através de um envolvimento consciente com o design e a arte manual do macramê. [resumo fornecido pelo autor]
Keywords: Design; Macrame; Slow Design